2014
DOI: 10.1007/s10995-014-1445-8
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and Depression in Mothers and Fathers of a Chronically Ill Child

Abstract: We aimed to determine the levels of anxiety and depression in mothers and fathers of a chronically ill child (0-18 years) and to study which parental and child variables are associated with anxiety and depression. In a cross-sectional design, anxiety and depression were assessed with the Hospital Anxiety and Depression Scale. Scores were compared to a Dutch reference group by analysis of variance and logistic regression analysis. Linear regression analyses were performed to examine which variables were associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
89
3
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(116 citation statements)
references
References 38 publications
14
89
3
3
Order By: Relevance
“…Van Oers et al [17] found that mothers of a chronically ill child (n = 566) scored significantly higher than the reference group (p < 0.001) on anxiety (mean 5.9 vs. 4.8) and depression (mean 4.5 vs. 3.1). Fathers (n = 123) had higher depression scores (mean 4.5 vs. 3.6; p < 0.05).…”
Section: Quality Of Lifementioning
confidence: 99%
“…Van Oers et al [17] found that mothers of a chronically ill child (n = 566) scored significantly higher than the reference group (p < 0.001) on anxiety (mean 5.9 vs. 4.8) and depression (mean 4.5 vs. 3.1). Fathers (n = 123) had higher depression scores (mean 4.5 vs. 3.6; p < 0.05).…”
Section: Quality Of Lifementioning
confidence: 99%
“…Findings suggest that after a diagnosis of SCII, parents suffer increased psychological distress (Bruce, 2006;Hall et al, 2006;Pai et al, 2007), are at higher risk of developing symptoms of depression and anxiety (Doherty et al, 2009;van Oers et al, 2014), and may be at risk for persisting psychiatric morbidity (Bryant, Creamer, O'Donnell, Silove, & McFarlane, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, sleep disturbance is associated with intense pruritus worsening at night (Williams, 1999). Chronic disease progression in children requires considerable parental care and, due to this, parents can experience very high levels of anxiety and depression (van Oers, 2014). Parents sleep with their children at night to prevent pruritus-induced scratching which may lead to bleeding and infection.…”
Section: Introductionmentioning
confidence: 99%